PERANAN FILSAFAT PADA PROGRAM PENDIDIKAN PROFESI GURU DALAM JABATAN ANGKATAN 3 (KAJIAN ONTOLOGI, EPISTOMOLOGI, DAN AKSIOLOGI) - Simanjuntak, Ruth Mayasari; Nurfatanah, Nurfatanah; Hanum, Faradilla (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2024)
The purpose of this study is to explore the role of philosophy in the in-service professional education program, batch 3, when viewed from the study of ontology, epistemology, and axiology. This type of research is qualitative research. This research method uses a case study method. The role of teachers in the education system is very important, not only as a transmitter of knowledge but also as a shaper of students' moral and ethical character. Teachers are required to continue to develop their competence to become professionals, per Law of the Republic of Indonesia Number 14 of 2005 which mandates academic qualifications, competence, certification, and physical and mental health. The Teacher Professional Education Program (PPG) aims to ensure that teachers have the required competence. This program is divided into pre-service PPG and in-service PPG, which are intended for teachers who are already actively teaching. This study focuses on in-service PPG batch 3 at HKBP Nommensen University. The results of the study are that the philosophy of education has an important role in the PPG program, providing a theoretical basis for improving teacher competence. Teachers can understand and apply ethical, moral, and scientific knowledge values ​​in teaching through the study of philosophy, including ontology, epistemology, and axiology. This research is expected to contribute significantly to the development of teacher competence.